Tracing the atom: nuclear legacies in Russia and Central Asia - Bauer, Susanne; Penter, Tanja (Taylor & Francis, 2022)
This book is about nuclear legacies in Russia and Central Asia, focusing on selected sites of the Soviet atomic program, many of which have remained understudied. Nuclear operations, for energy or military purposes, demanded a vast infrastructure of production and supply chains that have transformed entire regions. In following the material traces of the atomic programs, contributors pay particular attention to memory practices and memorialization concerning nuclear legacies. Tracing the Atom foregrounds historical and contemporary engagements with nuclear politics: How have institutions and governments responded to the legacies of the atomic era? How do communities and artists articulate concerns over radioactive matters? What was the role of radiation expertise in a broader Soviet and international context of the Cold War? Examining nuclear legacies together with past atomic futures and post-Soviet memory and nuclear heritage, sheds light on how modes of knowing intersect with livelihoods, compensation policies, and historiography. Bringing together a range of disciplines - history, science and technology studies, social anthropology, literary studies, and art history - this volume offers insights that broaden our understanding of 20th century atomic programs and their long aftermaths